2014
DOI: 10.1007/s11427-014-4742-y
|View full text |Cite
|
Sign up to set email alerts
|

Hsa-miR-1246, hsa-miR-320a and hsa-miR-196b-5p inhibitors can reduce the cytotoxicity of Ebola virus glycoprotein in vitro

Abstract: Ebola virus (EBOV) causes a highly lethal hemorrhagic fever syndrome in humans and has been associated with mortality rates of up to 91% in Zaire, the most lethal strain. Though the viral envelope glycoprotein (GP) mediates widespread inflammation and cellular damage, these changes have mainly focused on alterations at the protein level, the role of microRNAs (miRNAs) in the molecular pathogenesis underlying this lethal disease is not fully understood. Here, we report that the miRNAs hsa-miR-1246, hsa-miR-320a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 51 publications
0
31
0
Order By: Relevance
“…However, the major drawback with such potential drug regimens is the requirement of multiple doses for achieving the proper therapeutic efficacy, which is not ideal with regard to patient compliance and outbreak scenarios [66]. The microRNA (mi-RNAs: hsa-miR-1246, hsa-miR-320a, and hsa-miR-196b-5p) inhibitors have also been suggested to lower the cytotoxicity of Ebola virus glycoprotein in in vitro trials [76]. Nevertheless, more studies are needed before the final clearance and launch of any safe and efficacious antiviral drug in the global market, as considerable differences exist in the defence systems of human and small animal models, and therefore, the results of animal experimentations cannot be directly extrapolated for human beings.…”
Section: Treatmentmentioning
confidence: 99%
“…However, the major drawback with such potential drug regimens is the requirement of multiple doses for achieving the proper therapeutic efficacy, which is not ideal with regard to patient compliance and outbreak scenarios [66]. The microRNA (mi-RNAs: hsa-miR-1246, hsa-miR-320a, and hsa-miR-196b-5p) inhibitors have also been suggested to lower the cytotoxicity of Ebola virus glycoprotein in in vitro trials [76]. Nevertheless, more studies are needed before the final clearance and launch of any safe and efficacious antiviral drug in the global market, as considerable differences exist in the defence systems of human and small animal models, and therefore, the results of animal experimentations cannot be directly extrapolated for human beings.…”
Section: Treatmentmentioning
confidence: 99%
“…The GP protein of EBOV is responsible for receptor binding and fusion of the viral and cellular membranes. Recently, it has been reported to be able to mediate the level of certain microRNAs [3], which could be served as potential targets for Ebola drugs. Phylogenic analyses were performed using a Bayesian evolutionary analysis by sampling trees (Beast) approach [4], and 24 different combinations of molecular clock models (n=3) and coalescent models (n=8) were applied (Table S2 in Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…GP is considered as a viral determinant of EBOV pathogenicity and likely contributes to hemorrhage during infection, as several groups reported that overexpression of GP can induce cell detachment and rounding in vitro and ex vivo [2]. Similar results were also confirmed by Prof. Jiang and her colleagues [3].…”
mentioning
confidence: 99%
“…In the article published in this issue, Sheng et al [3] attempted to explore the molecule mechanism by which GP induces cell damage from a new angle. They evaluated the microRNA levels, using the RNA-Seq method, in human umbilical endothelial cells (HUVECs) that overexpress EBOV GP.…”
mentioning
confidence: 99%
See 1 more Smart Citation